Endoscopic findings in patients with dyspeptic symptoms (Research, Society and Development, 2021)
Introduction: Endoscopy has an important value to assess dyspeptic complaints. It is known that the findings seen on examination can determine the presence of structural diseases that justify such symptoms. Objective: Identify the prevalence of endoscopic findings in patients with dyspeptic symptoms. Methodology: Prospective, cross-sectional and descriptive study conducted in the city of Aracaju / SE, in patients who underwent EGD and a previous clinician of dyspepsia or dyspeptic complaints. Samples of 859 reports from individuals diagnosed with dyspepsia were used and sociodemographic and clinical questionnaires with open and closed questions were applied, as well as a questionnaire containing the ROMA III criteria. In the end, 847 were considered valid, 792 (93.5%) had some alteration, 36 (4.5%) reports were considered normal, that is, without structural damage and 19 (2.39%) of them did not were released by the patients. The median age group (IIQ) was 37 (30 to 46) years, 549 (64.8%) were female, 617 (72.8%) were from the capital. Among the endoscopic findings, the diagnosis of gastritis was statistically significant (p